THE ARTISTIC EXPRESSION OF TAPAN SHANTIKARI - Kumar, Sanjay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Tapan Shantikari started his artistic practice in 1968. Apart from being a skilled sculptor, he also made valuable contributions as an art teacher at Banaras Hindu University. Shantikari's work presents a unique amalgamation of Indian traditional aesthetics and modern artistic techniques, which is especially reflected in his sculptures and terracotta murals. We take a closer look at Shantikari's artistic practice, which includes creative experiments with various mediums such as terracotta, metal and stone. As a sculptor, Shantikari has created a distinct artistic style. His sculptures, especially his terracotta murals depicting the local culture of Banaras, include the ghats of Banaras, rivers, plants, birds, animals, and geometric and abstract shapes that highlight how he has incorporated the rich cultural heritage of Banaras in his artworks. The key objective of this paper is that Shantikari's art represents a significant contribution to Indian contemporary sculpture, bridging the gap between traditional themes and modern artistic expression. The influence of his work can be seen in a new generation of artists and provides valuable insights into the development of Indian sculpture in the late 20th century.